A new species of the velvetfish genus Cocotropus (Synanceiidae: Aploactininae) from the Philippines - Wada, Hidetoshi; Motomura, Hiroyuki (Zootaxa, 2026)
Cocotropus kanding sp. nov. (Synanceiidae: Aploactininae) is described on the basis of a single specimen (MNHN-IC 2025-0487, 42.4 mm standard length: SL) collected north of Panay Island, the Philippines, western Pacific Ocean. The new species is characterized by the following combination of characters: dorsal-fin rays XII, 10; anal-fin rays II, 6; pectoral-fin rays 13; segmented lower caudal-fin rays 6; total vertebrae 26; lacrimal spine short, its length 81.4% of upper-jaw length; pectoral fin short, its posterior tip not reaching anus; caudal fin short, its length 25.4% of SL; no papillae on posterior portion of upper jaw; 7 pairs of papillae on ventral surface of lower jaw; interneural space between 7th and 8th vertebrae lacking dorsal-fin spine proximal pterygiophores; bases of 1st–4th dorsal-fin spines anterior to 3rd neural spine; 5 preopercular spines; vomerine teeth absent; 2nd mandibular pores separated; body of preserved specimen with irregular dark smudges.